The influence of the psychological contract on the performance of inter-organizational networks: perspetive from behaviors of organizational citizenship - Correia, Rui (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
The objetive of this article is to show, conceptually, the relevance of the psychological contract in the performance of the functioning of inter-organizational networks, through its influence on the emergence of behaviours of organizational citizenship. The work contract can be perceived in two ways: the formal contract, described in the form of a written work contract, and the other, the informal and implicit psychological contract. A more favourable psychological contract is related to high levels of commitment and performance, making collaborators show a set of actions that are not directly related to their main functions, but which are important in modelling the organizational, social and psychological context that serves as a catalyst for task activities and processes. Various studies have revealed that organizations where behaviours of organizational citizenship are more marked show better indicators of effectiveness. It seems obvious to assume that organizational citizenship behaviours influence positively the performance of inter- organizational networks. But will it in fact be possible to establish some relationship between the results of inter-organizational networks and organizational citizenship behaviours, associated with organizational effectiveness? We explore the conceptual relationship between the dimensions of organizational citizenship – inter-personal harmony, spirit of initiative, conscientiousness and identification with the organization – and the results associated with the functioning of inter-organizational networks – strategic and economic benefits, learning and knowledge, innovation and transformations in the environment. After presentation of a conceptual model of analysis, we also present propositions to be explored in future investigations within this area of knowledge.